ANALISIS FORMULA DALAM NOVEL RUMAH UNTUK ALIE KARYA LENN LIU A FURMALIC ANALYSIS OF LENN LIU’S NOVEL, RUMAH UNTUK ALIE - NiLuh Gede Ani Sasmita Utari; I Nyoman Weda Kusuma; I Ketut Nama (CV. Adiba Aisha Amira, 2026)
This study aims to analyze the intrinsic element formula found in the popular novel Rumah Untuk Alie by Lenn Liu and to examine how this formula operates in influencing its popularity to achieve best-seller status. The novel, which originated as an Alternate Universe (AU) on social media and was later adapted into a film, strongly indicates its success as a popular literary product. The concept of popular literary formula (Cawelti, 1976), which represents dramatic conventions or narrative structures favored by the market, is used as the analytical framework. The research employs a descriptive qualitative method with library research (reading and noting) techniques on textual data in the form of quotes. The analysis results indicate that the theme of toxic family and trauma constitutes the most dominant core formula, driving other elements such as complex antagonist characters (The Father and The Four Older Brothers) and a progressive plot focusing on suffering and the search for a safe haven. This formula successfully captures reader attention due to its reflection of socially relevant issues regarding mental health and family relationships (social relevance), packaged in accessible everyday language, thereby establishing it as a best-seller formula product.